System analiz i prognoz (SAP) - narzędzie wizualizacji i przetwarzania danych - Suchecki, Bogdan; Gajdos, Artur (Data analysis and forecasting system - visualization and data processing tool, 2006)
Data Analysis and Forecasting System, which authors are the team from Chair of Spatial Econometrics, is the on-line information and forecasting system. System provides connections between databases, analytical tools and new, dynamic WWW technologies. Working in the system relay on calculations on statistical data and presentations results on-line. More information about actual version of the system: www.sap.uni.lodz.pl.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 74-82